Degradation of water quality due to heavy pollution in industrial area of Korba, Chhattisgarh - Upadhyay, Manish; Sahu, Bed Lal; Pardhi, Om Prakash (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">The present investigation were undertaken to study chemical & physical properties of Effluents discharged from korba Industrial area. Industrial waste if discharged into surface water can give rise to significant deterioration in its quality. This paper presents groundwater quality of korba industrial area in korba City. Nine different locations were selected for the study and compared. The parameters studied were pH, total alkalinity, total hardness, turbidity, chloride, sulphate, fluoride, total dissolved solids and conductivity. From overall analysis, it was observed that there was a slight fluctuation in the physico-chemical parameters among the water samples studied. Comparison of the physico-chemical parameters of the water sample with WHO and ICMR limits showed that the Surface water is highly contaminated and account for health hazards for human use .